Regulation of Ascorbate Accumulation and Metabolism in Lettuce by the Red:Blue Ratio of Continuous Light Using LEDs - Zha, Lingyan; Liu, Wenke; Yang, Qichang; Zhang, Yubin; Zhou, Chengbo; Shao, Mingjie (Frontiers in Plant Science, 2020)
Ascorbate (AsA), an antioxidant that cannot be synthesized or stored by the human body, plays an essential role in the proper functioning of both plants and humans. With the goal of increasing the AsA level in lettuce, the effects of different ratios of red (R) to blue (B) light (75R:25B, 50R:50B, and 25R:75B) on AsA pool sizes as well as the transcript levels and activities of key enzymes involved in AsA metabolism were constantly monitored for 12 days under continuous light (200 μmol·m-2·s-1) from LEDs. The results showed that lettuce biomass was positively correlated with the ratio of red light, while the AsA pool size had a positive correlation with the ratio of blue light during the whole experiment. The 25R:75B treatment increased the expression of genes involved in AsA biosynthesis (GMP, GME, GGP, GPP, GLDH) and regeneration (APX, MDHAR, DHAR, and GR) on day 3 but only significantly elevated the activities of enzymes involved in AsA regeneration (APX, MDHAR, DHAR, and GR) on days 6 and 9. AsA regeneration enzymes (MDHAR, DHAR and GR) had greater correlations with the AsA level than the AsA synthesis enzyme (GLDH). Thus, it is concluded that a high ratio of blue light elevated the AsA level mainly by promoting AsA regeneration rather than biosynthesis. In addition, altering the red:blue ratio of continuous light from high to low before harvest is recommended for lettuce cultivation to achieve both high yield and high quality.